Mediastinal T-Cell Lymphoblastic Lymphoma: A Rare Case in a Limited Resources Setting - Sutrisno, Sutrisno; Kusumastuti, Etty Hary; Ridholia, Ridholia; Hasan, Hasan (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2024)
Background: Lymphoblastic Lymphoma (LBL) is a rare neoplasm which represents 1-2% of all Non-Hodgkin’s Lymphomas (NHLs).Objectives: To present challenges in diagnostic of a rare case in limited resources settingCase Presentation: A 36-year-old male came to Dr. Soetomo hospital with shortness of breath, facial edema and chest pain. Physical examination revealed a decreased breath sound and dull percussion in the right chest. CT scan showed solid mass 10.4 x 5.9 x 14.6 cm in the anterior - medius of mediastinum. Fine needle aspiration biopsy guided by CT scan showed the spread of lymphoid cells, big in size, anaplastic, rounded and hyperchromatic nuclei. Core biopsy showed diffuse and monotonous pattern of pleomorphic cells, round to oval and hyperchromatic nuclei. Immunostaining were positive for CD3 and Tdt, high Ki67 proliferation index 98%, and negative for CD20.Conclusion: T-LBL is a rare neoplasm, that generally occurs in adolescents and young adults, and is most common in males. It is an aggressive neoplasm, which can involve mediastinal mass and cause superior vena cava syndrome. Immunostaining would be positive for Tdt, and variably express CD1a, CD2, CD3, CD4, CD5, CD7, and CD8. The prognosis was poor due to the aggressiveness and the relapse.